A non-enzymatic function of 17β-hydroxysteroid dehydrogenase type 10 is required for mitochondrial integrity and cell survival - Rauschenberger, Katharina; Schöler, Katja; Sass, Jörn Oliver; Sauer, Sven; Djuric, Zdenka; Rumig, Cordula; Wolf, Nicole I.; Okun, Jürgen G.; Kölker, Stefan; Schwarz, Heinz; Fischer, Christine; Grziwa, Beate; et al. (EMBO molecular medicine, 2010)
Abstract Deficiency of the mitochondrial enzyme 2-methyl-3-hydroxybutyryl-CoA dehydrogenase involved in isoleucine metabolism causes an organic aciduria with atypical neurodegenerative course. The disease-causing gene is HSD17B10 and encodes 17?-hydroxysteroid dehydrogenase type 10 (HSD10), a protein also implicated in the pathogenesis of Alzheimer's disease. Here we show that clinical symptoms in patients are not correlated with residual enzymatic activity of mutated HSD10. Loss-of-function and rescue experiments in Xenopus embryos and cells derived from conditional Hsd17b10?/? mice demonstrate that a property of HSD10 independent of its enzymatic activity is essential for structural and functional integrity of mitochondria. Impairment of this function in neural cells causes apoptotic cell death whilst the enzymatic activity of HSD10 is not required for cell survival. This finding indicates that the symptoms in patients with mutations in the HSD17B10 gene are unrelated to accumulation of toxic metabolites in the isoleucine pathway and, rather, related to defects in general mitochondrial function. Therefore alternative therapeutic approaches to an isoleucine-restricted diet are required.
Gesehen am 10.05.2023